Sedimentology of the Paleozoic limestone of the Kinta Valley, Peninsular Malaysia - B Pierson, Solomon Kassa, Haylay Tsegab, A Kadir, C Sum, Aaron H, . (2011)
The limestone hills of the Kinta Valley are remnants of extensive limestone beds, which are part of a Paleozoic carbonate complex that covered large parts of South-East Asia and south China.